(untitled) (Hekima Review, 2005)
In this book the author shows the impact and significance of the second Vatican Council in East Africa. The book is divided into four main parts. In the first part, the author presents the different forms of adaptation before Vatican II. The second part sheds light on the unfolding of Vatican II in East Africa. The third and fourth parts are concerned with the presentation of the role of Dutch missionaries in the implementation of the second Vatican Council in both the structural and the liturgical renewal.